Psychomotor Retardation in Elderly Untreated Depressed Patients - Beheydt, Lieve Lia; Schrijvers, Didier; Docx, Lise; Bouckaert, Filip; Hulstijn, Wouter; Sabbe, Bernard (Frontiers in Psychiatry, 2015)
Background: Psychomotor retardation (PR) is one of the core features in depression according to 17 DSM V1, but also aging in itself causes cognitive and psychomotor slowing. This is the first study 18 investigating psychomotor retardation in relation to cognitive functioning and to the concomitant 19 effect of depression and aging in a geriatric population ruling out contending effects of psychotropic 20 medication. Methods: A group of 28 non-demented depressed elderly is compared to a matched 21 control group of 20 healthy elderly. All participants underwent a test battery containing clinical 22 depression measures, cognitive measures of processing speed, executive function and memory, 23 clinical ratings of psychomotor retardation and objective computerized fine motor skill-tests. 24 Statistical analysis consisted of a General Linear Method (GLM) multivariate analysis of variance to 25 compare the clinical, cognitive and psychomotor outcomes of the two groups. Results: Patients 26 performed worse on all clinical, cognitive and psychomotor retardation measures. Both groups 27 showed an effect of cognitive load on fine motor function but the influence was significantly larger 28 for patients than for healthy elderly except for the initiation time. Limitations: due to the restrictive 29 inclusion criteria, only a relatively limited sample size could be obtained. Conclusion: With a 30 medication free sample, an additive effect of depression and aging on cognition and PR in geriatric 31 patients was found,. As this effect was independent of demand of effort (by varying the cognitive 32 load), it was apparently not a motivational slowing effect of depression.